Characteristics of rotating arc for CF4 removal. (8th December 2008) - Kim, Kwan-Tae; Song, Young-Hoon; Cha, Min Suk; Lee, Dae Hoon, Dong-Hyun Kim
Characteristics of CF4 treatment process with a rotating arc are investigated under different thermal and non-thermal plasma conditions. To generate high temperature or non-thermal plasma conditions, a rotating arc reactor is operated with various operating conditions, which are species of carrier gases, flow rates, and input power. Test results reveal that that high temperature conditions caused by CH4 and O2 addition is an effective approach for increasing CF4 removal efficiency. Non-thermal plasma conditions, however, do not result in noticeable increase in CF4 removal efficiencies despite supplying O2 or Ar gases into the process.